Objective response and time to progression on sequential treatment with sunitinib and sorafenib in metastatic renal cell carcinoma - Buchler, Tomas; Pavlik, Tomas; Bortlicek, Zbynek; Poprach, Alexandr; Vyzula, Rostislav; Abrahamova, Jitka; Melichar, Bohuslav (Medical oncology (Northwood, London, England), 2012)
Patients with metastatic renal cell carcinoma (mRCC) are often treated sequentially with targeted agents, although the optimal strategy is not known. A retrospective, registry-based study has been carried out to assess correlation between clinical response and progression-free survival in patients with mRCC treated sequentially with tyrosine-kinase inhibitors (TKIs) sunitinib and sorafenib. Data on 218 mRCC patients treated with sunitinib and sorafenib who completed therapy with both TKIs were obtained from a database of mRCC patients. Standard nonparametric methods were used to assess correlation between response, PFS and length of treatment on the two agents. A strong correlation between responses to first- versus second TKI was observed (p < 0.001). No significant association was noted between the duration of therapy with the two TKIs (p = 0.056), although there was a weak statistically significant correlation between progression-free survival times in the subgroup patients who discontinued treatment because of disease progression. In conclusion, the duration of response on first TKI is of limited value in selecting mRCC patients for sequential TKI therapy. There is a strong correlation between the types of tumour response on the first- versus the second TKI.
Keywords: senioři; Sorafenib; Phenylurea Compounds; Carcinoma, Renal Cell; Indoles; Sunitinib; Disease Progression; senioři nad 80 let; Niacinamide; Retrospective Studies; progrese nemoci; lidé; niacinamid; Middle Aged; mužské pohlaví; sorafenib; nádory ledvin; karcinom z renálních buněk; Adult; sunitinib; Kidney Neoplasms; Pyrroles; Aged, 80 and over; Disease-Free Survival; ženské pohlaví; retrospektivní studie; Humans; lidé středního věku; Antineoplastic Combined Chemotherapy Protocols; indoly; protokoly protinádorové kombinované chemoterapie; dospělí; Female; Aged; přežití bez známek nemoci; pyrroly; Male; fenylmočovinové sloučeniny